OPTIMALISASI PERAN PEMDA DALAM MENGATASI KENDALA PELAKSANAAN KONSERVASI KEANEKARAGAMAN HAYATI DI DAERAH (STUDI KASUS PROVINSI BENGKULU) - Antung Deddy Radiansyah (Jurnal Good Governance, 2020)
Gaps in biodiversity conservation management within the Conservation Area that are the responsibility of the central government and outside the Conservation Areas or as the Essential Ecosystems Area (EEA) which are the authority of the Regional Government, have caused various spatial conflicts between wildlife /wild plants and land management activities. Several obstacles faced by the Local Government to conduct its authority to manage (EEA), caused the number and area of EEA determined by the Local Government to be still low. At present only 703,000 ha are determined from the 67 million ha indicated by EEA. This study aims to overview biodiversity conservation policies by local governments and company perceptions in implementing conservation policies and formulate strategies for optimizing the role of Local Governments. From the results of this study, there has not been found any legal umbrella for the implementation of Law number 23/ 2014 related to the conservation of important ecosystems in the regions. This regulatory vacuum leaves the local government in a dilemma for continuing various conservation programs. By using a SWOT to the internal strategic environment and external stratetegic environment of the Environment and Forestry Service, Bengkulu Province , as well as using an analysis of company perceptions of the conservation policies regulatary , this study has been formulated a “survival strategy” through collaboration between the Central Government, Local Governments and the Private Sector to optimize the role of Local Government’s to establish EEA in the regions.Keywords: Management gaps, Essential Ecosystems Area (EEA), Conservation Areas, SWOT analysis and perception analysis